(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article is devoted to investigation of intangible motivation of the company’s personnel. Methods of non-material motivation in modern conditions are considered. At the same time, the author considers material motivation to be a necessary but insufficient condition for the development of enterprises and organizations. The essence of the concepts "motivation", "motive" and "stimulation" of labor activity is given. From the author’s point of view, the possibility of achieving success should be considered a priority motivator. The conditions for effective staff motivation are clarified. The main motives of work and methods of non-material motivation are revealed. The process of "demotivation" is characterized, a list of demotivational factors that directly affect the quality of staff work is given. The main theoretical and methodological principles of personnel motivation at the enterprise are considered. The contribution of the theory of emotional motivation as a type of behavioral economics, which is not based on a rational research paradigm, is indicated. Emphasis is placed on the priority role of intangible motivation and the features of its application in the activities of enterprises and organizations. The main types and tools of non-material motivation of personnel in today’s conditions are defined. Differences between material and non-material motivation are revealed. Recommendations for the formation of a personnel motivation system at the enterprise are given. It is noted that the practice of motivating personnel of modern organizations is a complex phenomenon which is complexly hierarchically organized. It is proven that in each situation it is necessary to apply an individual approach; at the same time, motivation for the development of modern personnel should be systematic, consistent and comprehensive. At the same time, it is important to have a fair and logical system for every organization. The motivation system should cover all hierarchical levels for different positions, have uniform principles of construction, supporting the organization’s strategy and goals.